Auroral Hiss Emissions During Cassini's Grand Finale: Diverse Electrodynamic Interactions Between Saturn and Its Rings. Issue 14 (24th July 2018) - Sulaiman, A. H.; Kurth, W. S.; Hospodarsky, G. B.; Averkamp, T. F.; Persoon, A. M.; Menietti, J. D.; Ye, S.‐Y.; Gurnett, D. A.; Píša, D.; Farrell, W. M.; Dougherty, M. K.
Abstract: The Cassini Grand Finale orbits offered a new view of Saturn and its environment owing to multiple highly inclined orbits with unprecedented proximity to the planet during closest approach. The Radio and Plasma Wave Science instrument detected striking signatures of plasma waves in the southern hemisphere. These all propagate in the whistler mode and are classified as (1) a filled funnel‐shaped emission, commonly known as auroral hiss. Here however, our analysis indicates that they are likely associated with currents connected to the rings. (2) First observations of very low frequency saucers directly linked to the planet on field lines also connected to the rings. The latter observations are unique to low altitude orbits, and their presence at the Earth and Saturn alike shows that they are fundamental plasma waves in planetary ionospheres. Our results give an insight, from a unique perspective, into the dynamic and diverse nature of Saturn's environment. Plain Language Summary: Cassini's high‐inclination Grand Finale orbits brought the spacecraft closer to Saturn than ever before, with the closest approach between the cloud tops and the inner edge of the D ring. This unprecedented set of orbits introduced a new view of Saturn's system by enabling direct measurements of the topside ionosphere as well as the rings' surrounding environment. Here we present evidence of communication between Saturn's ionosphere and rings via plasma waves. These results underline Saturn's system as one of the most dynamic and diverse in the solar system. Key Points: Striking auroral hiss emissions are observed in Saturn's southern hemisphere Ray tracing analysis confirms that auroral hiss emissions originate from the rings We report the first observations of VLF saucers directly associated with Saturn's ionosphere